Improving Student’s Listening Skill through Watching English Movies: English - Sirrul Bari; Muhammad Tazul (JOEY: Journal of English Ibrahimy, 2024)
The purpose of this research was to analyze and describe the improvement of students’s listening skills through watching English movies at MA Salafiyah Syafi'iyah. This objective aims to assess whether the use of English movies as a teaching tool has a positive impact on students' listening proficiency. Research using action was the classification chosen for this research. There were two meetings every cycle, and it was run in two cycles. The main subjects of the research were twenty-five eleventh graders at MA Salafiyah Syafi'iyah. Data were collected in both qualitative and quantitative forms. The qualitative information was gathered through student and English teacher interviews as well as observations. Meanwhile, both before and after implementation, the listening assessments conducted in Cycle I and Cycle II provided the quantitative data. The research's test findings demonstrated an improvement between the pre- and post-tests. This was evident from the increase. Data were collected in both qualitative and quantitative forms. The qualitative information was gathered through student and English teacher interviews as well as observations. Meanwhile, both before and after implementation, the listening assessments conducted in Cycle I and Cycle II provided the quantitative data in the mean scores of the students. The pre-test average was 65.92, whereas the initial post-test average for the first cycle was 77.6. The second post-test resulted in an average score of 88.96.